Revista Chilena de Historia Natural - Ojeda, Patricio
Revista Chilena de Historia Natural (RCHN) publishes original research dealing with past and present phenomena from organismic to higher levels of biological organization, considering both empirical and theoretical studies on all kinds of taxa and environments. The major areas covered by RCHN are: botany and zoology; physiological and behavioral ecology; population biology; community and ecosystem ecology; systematics, biogeography and evolution.